ALOKASI WAKTU IBU RUMAH TANGGA PENJUAL IKAN DI KELURAHAN LAPULU KECAMATAN ABELI KOTA KENDARI - Lini Quentin; Ima Astuty Wunawarsih; Suriana Suriana; Usman Rianse; Darsilan Dima (Jurusan Penyuluhan Pertanian FP UHO, 2025)
The increasing dual role of women, in which housewives not only perform domestic work but also engage in economic activities to help increase family income. The objective of this study is to ascertain the amount of time allocated by housewives who work as fish sellers in Lapulu Village, Abeli District, Kendari City. The study population consists of housewives in Lapulu Village who are involved in or work as fish sellers at Lapulu Market, totaling 20 individuals. The research sample was determined using the census method. The data were collected through the documentation method and interviews with a guided interview. The research variable was the time allocation of housewives who are fish sellers. The collected data were then subjected to a descriptive quantitative analysis. The results of the study indicate that the time allocation of housewives who are fish sellers in Lapulu Village, Abeli District, Kendari City, involves dual roles as household managers and business operators. The allocation of time among housewives who engage in fish selling activities reveals their dual role as both household managers and business operators. This finding suggests that the majority of their time is allocated to domestic tasks rather than to activities related to the sale of fish.